Anticoagulative activity of Commiphora gileadensis, aspirin, and heparin on blood coagulation profiles in naïve mice - Alhazmi, Ayman Saeed (International Journal of Health Sciences, 2023)
Objective: Commiphora gileadensis is a small tree under the genus Commiphora. Previous studies showed medical applications, such as antibacterial and antihypertensive, for C. gileadensis. Methods: Sixty naïve mice were classified into six groups: control, C. gileadensis sap-treated group, C. gileadensis methanol extract-treated group, C. gileadensis acetone extract-treated group, heparin-treated group, and aspirin-treated group. Blood samples from each mouse in the six groups were collected in EDTA, sodium citrate, and heparin tubes. The body weight of each mouse was measured at the beginning and end of the experiment. Furthermore, complete blood count, kidney and renal function tests, coagulation profiles, prothrombin time (PT), activated partial thromboplastin time (aPTT), international normalized ratio (INR), D-dimer, and fibrinogen concentrations were estimated for each mouse. Results: The sodium, potassium, chloride, blood urea nitrogen, creatinine, alanine transaminase, and aspartate transaminase levels did not show statistical differences between all groups. Moreover, PT, aPTT, and INR were prolonged in the C. gileadensis sap, methanol, and acetone extracts-treated mice compared with those in the heparin and aspirin-treated groups (P < 0.01). D-dimer and fibrinogen concentrations did not show significant statistical differences between all groups. Conclusion: The current study concludes that the C. gileadensis sap, methanol, and acetone extracts prolonged PT, aPTT, and bleeding time in naïve mice more than heparin and aspirin. This means that the C. gileadensis extracts may have antithrombotic activity and may be used in the future to resolve intravascular thrombosis in patients having prosthetic valves.